Smart Calculator 6.0 - Andu, Yusrina; Mohamed, Nadiah; Othman, Norlida; Ahmad, Siti Noor Dina; Mohd Ruslan, Siti Zaharah; Jaafar, Zuraida (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Smart Calculator 6.0 was held on 19 April 2025 at UiTM Cawangan Negeri Sembilan, Kampus Kuala Pilah to improve students’ understanding and use of scientific calculators in mathematics-related courses. Students from various programs participated through an independent learning approach using modules and submitting video demonstrations of calculator applications. The program helped students explore advanced calculator functions, improve problem-solving efficiency, and build confidence in preparing for quizzes, tests, and examinations.